2022
DOI: 10.15537/smj.2022.43.3.20210809
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic detection of carbapenemase production among gram negative bacteria isolated from hospital acquired infections

Abstract: Objectives: To identify the carbapenemase producing Gram-negative bacteria )GNB( by phenotypic methods and to confirm the presence of resistant genes using realtime polymerase chain reaction )PCR(. Methods:This was a prospective study carried out at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
(36 reference statements)
2
5
1
Order By: Relevance
“…More than one carbapenemase gene was detected among 79/80 Klebsiella isolates and in all E. coli isolates. These findings were similarly stated by other researchers [ 18 , 20 , 30 , 31 , 34 36 ]. Hereby, the high prevalence of more than one carbapenemase gene in Enterobacterales isolates may illustrate the hastily propagating resistance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More than one carbapenemase gene was detected among 79/80 Klebsiella isolates and in all E. coli isolates. These findings were similarly stated by other researchers [ 18 , 20 , 30 , 31 , 34 36 ]. Hereby, the high prevalence of more than one carbapenemase gene in Enterobacterales isolates may illustrate the hastily propagating resistance.…”
Section: Discussionsupporting
confidence: 91%
“…Several recent studies have reported similar results, in which carbapenem resistance was more prevalent in Klebsiella spp. than E. coli [8,[14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…These urges evaluating and regular updates on the sensitivity/specificity values of the existed phenotypic and genotypic diagnostic methods of the most common circulating CPGN pathogens. Although, the phenotypic detection and molecular characterization of CPGN pathogens had been previously reported in literature [13][14][15][16], still more studies are urgently required to validate the laboratory performance (sensitivity/specificity/positive predictive value/negative predictive value) of the respective phenotypic methods and to correlate them with the different types of carbapenemase enzymes [1,14]. Therefore, in this study we aimed to evaluate the performance of four major phenotypic approaches namely MHT, mCIM, BCT, combined disk test by EDTA (CDT) for detecting CPGN pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…45 Furthermore, other studies stated that bla NDM was the predominant gene. 46,47 The major differences were likely due to different geographic region, antibiotics policy in different health care settings and methods of gene identification. 48 In our study, more than one resistance gene was detected in different isolates.…”
mentioning
confidence: 99%